Effect Of Oxytocin Massage On Milk Production In Pospartum Mothers Post SC 2 At Sawerigading Hospital Palopo - Nurhasanah; Warlindah; Helmi Nince Bernadus Coebraad (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2022)
Newborns need optimal care from birth, one of which is the ideal food. Newborn babies do not need other intakes other than breast milk from their mothers. But in reality, exclusive breastfeeding is not as easy as imagined. Various obstacles can arise to providing exclusive breastfeeding for the first six months of a baby's life. o, determine the effect of oxytocin massage on breast milk production in postpartum mothers at Sawerigading Palopo Hospital in 2021